Systemic treatment of brain metastases in non-small cell lung cancer. (June 2020) - Page, Simon; Milner-Watts, Charlotte; Perna, Marco; Janzic, Urska; Vidal, Natalia; Kaudeer, Naila; Ahmed, Merina; McDonald, Fiona; Locke, Imogen; Minchom, Anna; Bhosle, Jaishree; Welsh, Liam; et al.
Abstract: Brain metastases (BrMs) are associated with significant morbidity and are found in up to 50% of patients with advanced non-small cell lung cancer (NSCLC). Most of the literature focuses on symptomatic BrMs, with a lack of baseline brain imaging in asymptomatic patients. Unfortunately, much of the data on local treatments with or without systemic treatment is retrospective. Clinical trials of systemic treatments largely exclude patients with BrMs. Chemotherapy is an active treatment for BrM with response rates in the brain similar to other sites of disease. Targeted systemic treatments in patients with driver mutations (EGFR and ALK-MET to date) have impressive central nervous system (CNS) penetrance and response rates. Unfortunately, no prospective data can currently guide the timings or modality of local therapies with systemic treatments in these patients who have a high incidence of CNS disease, but retrospective data suggest that early local therapies may give better intracranial progression-free survival (ICPFS). Recent immunotherapy trials have included patients with BrMs. These patients have largely been pre-treated with local therapies and are asymptomatic. Thus, the current standard is becoming, early local therapies before or in conjunction with immunotherapy agents. The approach seems to be safe. Prospective studies are needed in NSCLC BrMs patients to make sure any benefit from local therapies on the ICPFS and quality of life is not overlooked. Here we report what we think are reasonable conclusions from the available data and make suggestions for future clinical trials in the management of NSCLC BrMs. Highlights: Brain metastases occur in 30% of patients with advanced NSC lung cancer. This percentage can be higher in those with driver mutations. Whether asymptomatic disease progresses to symptomatic disease is not known. We do not know if asymptomatic disease should be treated early. There are many reported series of patients, but most are retrospective with mixed patient populations. Prospective CTs are needed to ensure we are not missing benefit from addition of local therapy to systemic therapy.